Error analysis in EFL writing classroom - Karim, Abdul; Mohamed, Abdul R.; Ismail, Shaik A. M. M.; Shahed, Faheem H.; Rahman, Mohammad Mosiur; Haque, Md. Hamidul (© 2018 Canadian Center of Science and Education, 2019)
This article was published in the International Journal of English Linguistics [© 2018 Canadian Center of Science and Education] and the definite version is available at: https://doi.org/10.5539/ijel.v8n4p122 The Journal's website is at: http://www.ccsenet.org/journal/index.php/ijel/article/view/73383